Purepecha Immigrant Picking Lemons - Bacon, David
SANTA PAULA, CA - A crew of limoneros, or lemon pickers, is made up of indigenous Purepecha immigrants from Turiquaro, a town in the Mexican state of Michoacan, and indigenous Nahuatl immigrants from San Marcos in the state of Guerrero. Pictured: Edgar Felipe Jimenez, a Purepecha lemon picker.